2020
DOI: 10.1021/acs.jpcc.9b10142
|View full text |Cite
|
Sign up to set email alerts
|

NAP-XPS and In Situ DRIFTS of the Interaction of CO with Au Nanoparticles Supported by Ce1–xEuxO2 Nanocubes

Abstract: Control of metal–support interactions is one of the major challenges in heterogeneous catalysis. In this study, we explored the effect of Eu doping on the metal–support interactions in Au/Ce1–x Eu x O2 catalysts applied in the oxidation of CO. We probe the catalysts with CO under realistic conditions by near-ambient-pressure X-ray photoelectron spectroscopy (NAP-XPS) and in situ diffuse reflectance infrared Fourier transform spectroscopy (DRIFTS). NAP-XPS allows in situ investigation of the surface reducibilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 47 publications
(111 reference statements)
1
24
0
Order By: Relevance
“…This suggests that oxygen from Ce–O–Cu–O–Ce (−Ce–□–Cu–O–Ce) bridge is used for oxidation of CO to CO 2 , which agrees with the observed reduction of Ce 4+ to Ce 3+ as evident from Figure . A similar effect has been reported by Bezkrovnyi et al, who observed that Au nanoparticles facilitate the surface reduction of ceria in Au-doped CeO 2 under CO flow conditions …”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…This suggests that oxygen from Ce–O–Cu–O–Ce (−Ce–□–Cu–O–Ce) bridge is used for oxidation of CO to CO 2 , which agrees with the observed reduction of Ce 4+ to Ce 3+ as evident from Figure . A similar effect has been reported by Bezkrovnyi et al, who observed that Au nanoparticles facilitate the surface reduction of ceria in Au-doped CeO 2 under CO flow conditions …”
Section: Resultssupporting
confidence: 87%
“…Figure illustrates the corresponding Ce 3d region. The spectra can be deconvoluted into three doublets for Ce 4+ ( u ‴/ v ‴ at about 917 and 898.3 eV, u / v at 901.1 and 882.5 eV, and u ″/ v ″ at 907.7 and 887.6 eV, marked in red) and two doublets for Ce 3+ ( u ′/ v ′ at 903.6 and 884.8 eV and u 0 / v 0 at 899.2 and 880.6 eV, marked in blue). , The surface percentage of Ce 3+ (indicated on the right of the spectra in Figure ) was determined from the area of the subpeaks using eq . The surface of the bare support at 25 °C in He contains already 16.1% of Ce 3+ , confirming its surface reducibility in agreement with previously reported results. ,, This is also supported by the axial EPR signal with g ⊥ = 1.963 and g || = 1.941 in the bare support, assigned to electrons trapped in vacancies next to Ce 3+ (Figure ). Incorporation of Cu in Cat2 raises the Ce 3+ content to 29.5%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It remains an open question about the presence/absence of highly active subnanometer Au clusters in these samples. However, we observed the presence of such Au clusters in Au/CeO 2 (NC) annealed at 300 °C [32,33]. There are no objective reasons which can prevent thermally induced redispersion (e.g., strong anchoring on oxygen vacancies) in all investigated samples (annealed in the air only).…”
Section: Co Proxmentioning
confidence: 70%
“…It can be explained by the presence of highly active sub-nanometer Au nanoclusters in pre-treated samples (both at 300 and 500 °C). In our previous works, we observed, using (S)TEM technique, such Au clusters in Au/ CeO 2 (NC) annealed at 300 °C [32,33]. The second possible explanation is the presence of pseudo-single sites, i.e., gold ions slightly abstracted from a gold clusters, which exhibit lower activation energy in the rate-determining step of COoxidation [34].…”
Section: Co-oxidationmentioning
confidence: 87%